PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN TUALANG KABUPATEN SIAK (STUDI PENGURUSAN e-KTP) - Dwi Pratiwi Putri; Raden Imam Al Hafis (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Integrated Subdistrict Administrative Services have a role in providing servants in the District wilaya, among others, the service for handling e-KTP. Therefore, the implementation of e-KTP management services must optimize the form of service provided through Requirements, Procedures, Time, Products, Complaints. Public services are expected to be carried out in all matters including services in the management of e-ID cards at the Tualang Sub-District Office, Siak Regency. The purpose of this study was to analyze the service of administering the e-KTP at the Tualang Sub-District Office in Siak Regency and find out the obstacles in the service of the e-KTP Management at the Tualang Sub-District Office in Siak Regency. The results of this study are expected to provide the following benefits: contribution of the mind in order to develop science, especially in the field of social and political sciences as well as references to improve services, especially in the Management of e-KTP at the Tualang Sub-District Office, Siak Regency. The results of the research conducted at the Tualang Sub-District Head Office in Siak Regency through five indicators were in the category "Good Enough" with a value of 26 or a percentage of 57%. However, the author recommends to the employees of the Tualang Sub-District Office of Siak Regency in providing e-KTP Management services in order to improve the quality and quality of services in order to achieve better service.